Study Of Substitute Toxicity And General Pharmacological Activity Of The “Flukam” - Alimkulova Komila Zokirovna, Urmanova Flyura Faridovna, Imamaliev Alisherovich Bakhtiyor, Eryigitov Temurbek Rayimberdievich, Isadjanov Muzaffar Sunnatovich (International Journal of Advanced Science and Technology, 2020)
Subacute toxicity and general pharmacological activity of the dry extract “Flukam” were studied.